Microplastic contamination in market bivalve Argopecten purpuratus from Lima, Peru - Gabriel De-la-Torre; Lisseth Mendoza-Castilla; Rosa Pilar (Manglar)
Microplastics (< 5 mm) are ubiquitous contaminants in the marine environment. Many marine commercial species, among fish, mollusks and crustaceans, are subject to microplastic exposure through ingestion. The aims of the present study were to determine microplastic contamination in scallops from fishery markets of Lima and if microplastics are more likely to adhere to certain parts of the scallop. Argopecten purpuratus specimens were bought from fishery markets in Lima. Soft tissues were digested using 10% KOH and incubated at 60 °C overnight. An optical microscope was used to observe microplastics after vacuum filtration of the supernatant solution. Microplastic concentration, color and type were recorded. ATR-FTIR analysis determined the specific polymer types. The overall mean microplastic concentration was 2.25 ± 0.54 MP.ind-1. Fibers were the most abundant microplastic type, while red and blue were dominant colors. Mann Whitney U test indicated no significant differences (P > 0.05) of microplastic content between gonads and muscle. Microplastics in seafood and foodstuff could pose a threat to food security and human health. Still, information regarding microplastic pollution is scarce.